2010
DOI: 10.1111/j.1582-4934.2010.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human adipose‐derived stem cells into beating cardiomyocytes

Abstract: Human adipose-derived stem cells (ASCs) may differentiate into cardiomyocytes and this provides a source of donor cells for tissue engineering. In this study, we evaluated cardiomyogenic differentiation protocols using a DNA demethylating agent 5-azacytidine (5-aza), a modified cardiomyogenic medium (MCM), a histone deacetylase inhibitor trichostatin A (TSA) and co-culture with neonatal rat cardiomyocytes. 5-aza treatment reduced both cardiac actin and TropT mRNA expression. Incubation in MCM only slightly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(131 citation statements)
references
References 31 publications
(73 reference statements)
3
124
0
4
Order By: Relevance
“…22-24 On the other hand, ASC are also reported to be able to differentiate into cardiomyocytes. 25 Therefore, ASC and BM-MSC both might improve cardiac function by supplementing cardiomyocytes, as well as in a paracrine manner, although we did not investigate differences in differentiation into cardiomyocytes between them.…”
Section: Discussionmentioning
confidence: 99%
“…22-24 On the other hand, ASC are also reported to be able to differentiate into cardiomyocytes. 25 Therefore, ASC and BM-MSC both might improve cardiac function by supplementing cardiomyocytes, as well as in a paracrine manner, although we did not investigate differences in differentiation into cardiomyocytes between them.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue biopsies and lipoaspirate were digested to isolate the ASC population, as previously described [24]. In brief, the biopsies were rinsed during transportation from the operating room in Dulbecco's modified Eagle's medium (DMEM; low glucose), transferred to a digestive solution composed of 0.3% collagenase type I, 60 U/ml dispase II, and 1% penicillin/ streptomycin in low-glucose DMEM, minced with forceps, and allowed to incubate at 37°C for 30 minutes.…”
Section: Stem Cell and Progenitor Isolationmentioning
confidence: 99%
“…Previous studies by Muller-Borer et al (2004) suggested that synchronized Ca 2+ signalling via GJIC co-cultured with neonatal cardiomyocytes induces rat liver stem cells to express cardiac transcription factors and acquire a phenotype resembling cardiomyocytes (Anderson et al, 2007;Muller-Borer et al, 2004). Similarly, we have recently shown gap junctions established between human adiposederived MSC and neonatal rat cardiomyocytes in co-culture, which induces the expression of cardiac genes and spontaneous cardiomyocyte-like contractions in the human cells (Choi et al, 2010a) (Figure 2). All this points to a growing appreciation of the role of gap-junctionmediated Ca 2+ waves in modulating gene expression and promoting differentiation of stem cells.…”
Section: What Goes Through Gap Junctions and How Can This Modify Stemmentioning
confidence: 91%